Empirical Evaluation of Computer-Adaptive Alternate Short Forms for the Assessment of Anomia Severity - Hula, William D. (J Speech Lang Hear Res, 2019)
PURPOSE: The purpose of this study was to verify the equivalence of 2 alternate test forms with nonoverlapping content generated by an item response theory (IRT)–based computer-adaptive test (CAT). The Philadelphia Naming Test (PNT; Roach, Schwartz, Martin, Grewal, & Brecher, 1996)was utilized as an item bank in a prospective, independent sample of persons with aphasia. METHOD: Two alternate CAT short forms of the PNT were administered to a sample of 25 persons with aphasia who were at least 6 months postonset and received no treatment for 2 weeks before or during the study. The 1st session included administration of a 30-item PNT-CAT, and the 2nd session, conducted approximately 2 weeks later, included a variable-length PNT-CAT that excluded items administered in the 1st session and terminated when the modeled precision of the ability estimate was equal to or greater than the value obtained in the 1st session. The ability estimates were analyzed in a Bayesian framework. RESULTS: The 2 test versions correlated highly (r = .89) and obtained means and standard deviations that were not credibly different from one another. The correlation and error variance between the 2 test versions were well predicted by the IRT measurement model. DISCUSSION: The results suggest that IRT-based CAT alternate forms may be productively used in the assessment of anomia. IRT methods offer advantages for the efficient and sensitive measurement of change over time. Future work should consider the potential impact of differential item functioning due to person factors and intervention-specific effects, as well as expanding the item bank to maximize the clinical utility of the test. SUPPLEMENTAL MATERIAL: https://doi.org/10.23641/asha.11368040